Exploring Dominant Derivational Suffixes and Their Rhetorical Purposes in Motivational Speech - Abelia Silvana Zulva; Afrianto (Universitas Islam Negeri Palopo, 2026)
This study analyzes the use of derivational suffixes in Emily Jaenson’s speech to understand how morphological processes contribute to rhetorical meaning within motivational discourse. Using a qualitative descriptive approach, the research examines 17 derivational suffixes found in the speech, including those forming nouns from verbs (-ion, -ment, -ance), nouns from adjectives (-ship), adjectives from a noun (-ful), and a suffix forming adverbs from adjectives (-ly). The analysis specifically focuses on how these derivational forms function in shaping the speaker’s message about confidence building, personal development, and professional growth by knowing the dominant use of derivational suffixes in Emily Jaenson’s speech and what their rhetorical effects are on the meaning conveyed. The findings show that nouns formed through dominate the speech, such as celebration, recollection, decision, promotion, action, accomplishment, management, engagement, performance, and leadership. These nouns help the speaker talk about big ideas instead of just actions, so the audience focuses on thinking, learning, and personal growth. Each noun has a special meaning and most of those words have the same purpose in meaning. The results show that derivational suffixes are not only language features but also persuasive tools that make the speech more motivational. By creating nouns that describe processes, progress, and achievements, the speaker builds a message that inspires the audience to think about their own development. The study concludes that derivational suffixes are important for making ideas clear, keeping the audience engaged, and supporting the motivational message of the speech.